Serum β HCG and lipid profile in early second trimester as predictors of hypertensive disorders of pregnancy - Arora, Neetu; Sharma, Bhawna; Gupta, Shashi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Hypertensive disorders complicating pregnancy are common (5-10%) and form one member of the deadly triad, along with haemorrhage and infection that contribute greatly to maternal morbidity and mortality rates. Although overt illness rarely appears until third trimester, there are multiple indications that the disease process begin early in the pregnancy. Since years there has been a search for an early predictor of PIH so that special antenatal care can be given to these patients. This prospective study was one of the efforts to predict preeclampsia by measuring serum beta HCG levels and lipid profile in 2nd trimester of pregnancy. Methods: This was a prospective study carried out on 200 pregnant women attending the outpatient antenatal clinic and estimating serum beta HCG and lipid profile in early second trimester. Results: Most of the women who entered the study were in the age group of 21-30 years. Out of 200 patients, 164 remained normotensive and 36 turned out to be hypertensive. 50% of patients in the normotensive group and 75% in the hypertensive group were primigravidas indicating that primigravidas have a higher risk of developing PIH compared to multiparas. No correlation was found between the residence and occurrence of hypertension. Among 45 patients with beta HCG >40,000mIU/mL, 30 developed hypertensions, whereas, among 155 patients who had levels <40,000 mIU/mL, only 6 developed hypertension (p<0.0001). Maximum number of cases among the hypertensive group (83.33%) had serum TG levels >200 mg/dl. Among the hypertensive group, 83.4% cases had levels >250 mg/dl. A significantly higher number of hypertensive cases i.e.75% had serum VLDL >40 mg/dl. 83.4% of hypertensive patients had serum LDL >140 mg/dl. In our study, 5.5% of the cases among normotensive group had serum HDL <40 mg/dl whereas, 16.6% of cases among the hypertensive group had serum HDL <40 mg/dl. Conclusions: Women with raised serum beta HCG and/or dyslipidemia should be carefully followed up to achieve a more favourable outcome for both mother and the fetus.